Catalytic Effect of Potassium Compounds in Soot Oxidation. Issue 18 (9th June 2017) - Rinkenburger, Alexander; Toriyama, Takaaki; Yasuda, Kazuhiro; Niessner, Reinhard
Abstract: The combustion temperatures of soot in particulate filters can be decreased to exhaust gas temperatures by using catalysts. In addition to oxidic catalysts, alkali metal salts are very effective catalysts. Although soot is one of the world's most unwanted byproducts, combustion is still not fully understood. In this study, different soot mixed internally with salt samples were produced. All salts lead to a marked, salt‐ and salt‐content‐dependent decrease of the temperature‐programmed oxidation temperatures of maximum CO + CO2 emissions ( T max ), with K2 CO3 being one of the most effective catalysts that leads to a decrease of the T max of up to 300 °C. Structural parameters of the internally mixed soot derived by using Raman microspectroscopy, SEM, and scanning mobility particle size analysis did not change significantly; BET areas showed slight trends to lower areas with increased salt content, but no substantial correlations were observed. In contrast, a correlation of the oxidation reactivity to the number distribution of the measured actual fringe lengths by using high‐resolution transmission electron microscopy and the peak areas measured by using EPR spectroscopy was found. Salts lead to a narrowing of the actual fringe length number distributions to lower sizes and to reduced EPR peak areas. This demonstrates that the salts influence the nanostructure of the graphene planes by shortening the planes and further substantiates that soot oxidation is at least partly based on electron transfer and not only oxygen transfer. EPR spectroscopy measurements indicate that the oxidation mechanism is based on a temperature‐dependent chemical equilibrium, which depends on the K + /anion binding strength. Abstract : Soot, salt, and spectroscopy : The world's energy supply still relies largely on fossil fuels, with soot being one of the most unwanted byproducts of combustion. This study shows how alkali metal compounds can influence and enhance the oxidation reactivity of soot and gives new indications towards a more comprehensive understanding of combustion processes.